ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH PADA INVESTASI EMAS MELALUI APLIKASI PEGADAIAN DALAM PERSPEKTIF BISNIS ISLAM - Bela Mawarni; Ridwansyah Ridwansyah; Heni Verawati (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the factors that influence customer interest, experience and knowledge in investing in gold through the Pegadaian application from an Islamic business perspective. The method used is descriptive qualitative with direct field research at the Unit Pegadaian Cabang (UPC) Pahoman Bandar Lampung and literature studies which include interviews, observations, and literature analysis. Data were collected through purposive sampling techniques from customers who use the Pegadaian Digital Service (PDS) application as well as through documentation studies and related literature. The results showed that knowledge, experience, perceived ease of use, and Islamic business values such as transparency and fairness have a good influence on interest in investing in gold through the Pegadaian application. In addition, trust in transaction security and financial factors are also key determinants. This finding confirms that the integration of sharia aspects and ease of technology is an important factor in encouraging customer interest in investing in gold digitally through the Pegadaian application.